In-situ and ex-situ microstructure studies and dislocation-based modelling for primary creep regeneration response of 316H stainless steel. (1st September 2021) - Li, X.; Holdsworth, S.R.; Kalácska, S.; Balogh, L.; Park, J.-S.; Dasilva, Y. Arroyo Rojas; Maeder, X.; Cocks, A.; Mazza, E.; Hosseini, E.
Abstract: The emergence of renewable energy sources with their variable and unpredictable nature, in addition to the variation of energy need for weekdays vs. weekends, demands an ever flexible operation of thermal power plants. Such a feature has therefore altered the typical steady creep loading of high-temperature components of power plants to stress-varying or cyclic creep conditions. The introduced load transients have been found to affect the strain hardening memory of the creeping alloys and might lead to multiple primary creep regeneration (PCR). Therefore, the creep strain accumulation can considerably increase under such conditions. Consideration of the PCR phenomenon is beyond the capability of conventional creep constitutive models which are based on strain- or time-hardening assumptions. The present study conducted in-situ and ex-situ experiments for 316H stainless steel. Various microstructural examination techniques, such as synchrotron high energy X-ray and neutron diffraction, and backscattered and transmission electron microscopy, have been employed for characterising evolution of the dislocation structure and the internal lattice strain/stress state of the alloy during stress-varying and cyclic creep conditions. The formation/annihilation of dislocation pileups and the bowing/unbowing of dislocation-lines were identified as the responsible mechanisms for PCR. A dislocation-based model was then formulated which could well represent the measured microstructural evolution and mechanical response of the steel during the conducted experiments at 650°C. Graphical abstract: Image, graphical abstract